(untitled) (Stamford Journal of Microbiology, 2023)
Textile and clothing industries are major contributor to the economic growth in Bangladesh. Establishment of a number of such industries are imparting huge amount of industrial waste containing different types of chemicals including dyes. Pollutants generated from textile industries creates a huge burden on the environment. Textile industries discharge effluents containing various harmful chemicals including synthetic dyes that are very stable and a threat to living organisms. Bacillus spp. are remarkable bacteria which demonstrated potential to produce diverse kinds of metabolites for different uses. This study focuses on the potential use of Bacillus spp. isolated from the garden soil of Stamford University Bangladesh for decolorization of BemacronBlue RS (BB) and BemacronRed RS 01 (BR) dyes. Four Bacillus isolates were screened out from garden soil and named as 1B, 3A, 2C and 4B. Isolates were subjected to decolorization assay with 0.002 gm/l of BB and BR dyes. Bacillus spp. showed great potential in decolorizing BB and BR dyes, which was initiated after 2 days of incubation. Following 8 days of incubation, decolorization of BB was, 79%, 80%, 75%, 77% and BR was, 75%, 73%, 69%, 89% by the isolates 1B, 3A, 2C and 4B, respectively. This study shed some light on the potential use of indigenous garden bacteria for decolorization of textile dyes to control environmental pollution. Stamford Journal of Microbiology, 2023. Vol. 13, Issue 1, p. 1-5